Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Mechanisms of Strong Hearts, Healthy Communities-2.0 Effects on Weight: A Mediation Analysis - Chad D. Rethorst; Margaret Demment; Meredith L. Graham; Seungyeon Ha; Alexandra L. MacMillan Uribe; Brian K. Lo; Jacob Szeszulski; Phrashiah Githinji; David Strogatz; Sara C. Folta; Miriam E. Nelson; Rebecca A. Seguin-Fowler (Journal of Nutrition Education and Behavior, 2026)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Two applications of the Consensus Solutions process with collaborative modeling for management of a contentious oyster fishery - Elizabeth W. North; Michael J. Wilberg; Jeff Blair; Lisa Wainger; Jeffrey C. Cornwell; Robert Jones; Chris Hayes; Rasika Gawde; Raleigh Robert Hood; Taylor Goelz; Troy Hartley; Marvin M. Mace; et al. (Frontiers in Marine Science, 2024)
Worldwide, enhancement of oyster populations is undertaken to achieve a variety of goals including support of food production, local economies, water quality, coastal habitat, biodiversity, and cultural heritage. Although numerous strategies for improving oyster stocks exist, enhancement efforts can be thwarted by long-standing conflict among community groups about which strategies to implement, where efforts should be focused, and how much funding should be allocated to each strategy. The objective of this paper is to compare two engagement approaches that resulted in recommendations for multi-benefit enhancements to oyster populations and the oyster industry in Maryland, U.S.A., using the Consensus Solutions process with collaborative simulation modeling. These recommendations were put forward by the OysterFutures Workgroup in 2018 and the Maryland Oyster Advisory Commission (OAC) in 2021. Notable similarities between the efforts were the basic principles of the Consensus Solutions process: neutral facilitation, a 75% agreement threshold, the presence of management agency leadership at the meetings, a scientific support team that created a management scenario model in collaboration with community group representatives, numerous opportunities for representatives to listen to each other, and a structured consensus building process for idea generation, rating, and approval of management options. To ensure meaningful representation by the most affected user groups, the goal for membership composition was 60% from industry and 40% from advocacy, agency, and academic groups in both processes. Important differences between the processes included the impetus for the process (a research program versus a legislatively-mandated process), the size of the groups, the structure of the meetings, and the clear and pervasive impact of the COVID-19 pandemic on the ability of OAC members to interact. Despite differences and challenges, both groups were able to agree on a package of recommendations, indicating that consensus-based processes with collaborative modeling offer viable paths toward coordinated cross-sector natural resource decisions with scientific basis and community support. In addition, collaborative modeling resulted in ‘myth busting’ findings that allowed participants to reassess and realign their thinking about how the coupled human-oyster system would respond to management changes.

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

The FishPath approach for fisheries management in a data‐ and capacity‐limited world - Natalie A. Dowling; Jono R. Wilson; Jason M. Cope; Dawn T. Dougherty; Serena Lomonico; Carmen Revenga; Brian J. Snouffer; Natalio Godoy Salinas; Felipe Torres‐Cañete; Rowan C. Chick; Ashley M. Fowler; Ana M. Parma (Fish and Fisheries, 2023)
Successful fisheries management systems tend to be underpinned by harvest strategies, specifying formally agreed data collection systems, assessment approaches and management measures used to regulate fishing pressure. While harvest strategies can be effective even in data‐ and capacity‐limited (DCL) situations, their development remains challenging in such contexts. We present a process and decision‐support tool, FishPath, to guide the identification of suitable harvest strategy component options given often debilitating conditions: (i) resource limitations and lack of technical management capacity; (ii) ‘uniqueness’ of DCL fisheries; (iii) the concept of harvest strategies is unfamiliar to managers and scientists, and the universe of options is hard to navigate; and (iv) the lack of an effective participatory process to identify solutions tailored to local contexts. These conditions can lead to either management paralysis or generic solutions that may be poor fits to specific conditions. The FishPath Tool uses a diagnostic questionnaire that elicits the key characteristics and specific circumstances of a fishery. It compares these with the requirements of alternative options from an inventory of possible harvest strategy components, identifies where these requirements are met and provides customised, transparent guidance on the appropriateness of component options of a harvest strategy, specific to the fishery of interest and its governance context. The FishPath Process is a facilitated multi‐stakeholder, participatory engagement process aimed to set fisheries on the path to develop a harvest strategy. The FishPath Process and Tool combine to ensure a bottom‐up, documented, transparent, replicable and efficient process.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

Exploring new alleles for frost tolerance in winter rye - Wiltrud Erath; Eva Bauer; D. Brian Fowler; Andres Gordillo; Viktor Korzun; Mira Ponomareva; Malthe Schmidt; Brigitta Schmiedchen; Peer Wilde; Chris-Carolin Schön (Theoretical and Applied Genetics, 2017)

Metabolic Profiling of Human Long-Term Liver Models and Hepatic Clearance Predictions from In Vitro Data Using Nonlinear Mixed-Effects Modeling - Nicole A. Kratochwil; Christophe Meille; Stephen Fowler; Florian Klammers; Aynur Ekiciler; Birgit Molitor; Sandrine Simon; Isabelle Walter; Claudia McGinnis; Johanna Walther; Brian Leonard; Miriam Triyatni; et al. (The AAPS Journal, 2017)

Developmental regulation of metabolites and low temperature tolerance in lines of crosses between spring and winter wheat - Mohsen Hosseini; Reza Maali-Amiri; Siroos Mahfoozi; David Brian Fowler; Rahmat Mohammadi (Acta Physiologiae Plantarum, 2016)

Global Competency and Issues in Contemporary Education / Agroforestry - Susan Moore; Erin Sills; Lee Allen; Douglas Frederick; Frederick Cubbage; John Garland; Julie Lydick; Gordon Holley; Jodi Roberts; Stephen Grado; Zhu Ning; Shannon Fowler; et al. (Journal of Forestry, 2011)
34We performed a five year integrated research, extension and education project aimed at strengthening global competence of students and faculty through collaboration in forestry. We sought to improve our students' ability to cooperate, increase their understanding of global dynamics of forestry markets and enhance their knowledge of various approaches to forest management and conservation with Chile as the focus. The project had four key components: (1) facilitate faculty and student involvement in Chile through Spanish language training, a website, and visits by Chilean faculty; (2) support NC State faculty and student research and study in Chile through travel grants and study tours; (3) build on faculty sabbaticals in Chile by funding student research assistants; and (4) disseminate information from Chile through multiple channels to both the university and professional communities. The faculty exchange visits; graduate student research; and participation of NCSU students, faculty and staff in the study tours to Chile had substantial effects when the participants returned to the US and disseminated information about their experiences through both formal and informal mechanisms. Both students and faculty at NCSU are more aware of forestry research, policy and management in Chile. Faculty at NCSU and Chilean universities Universidad de Concepción and Universidad de Austral have established a strong basis for collaboration and are continuing to work together on funding proposals, research, and papers. Students who participated in the study tours learned about both the culture and forestry in Chile, including similarities, differences, and lessons for the US. This presentation will describe the activities, outcomes and ongoing impacts of the project.

Contrasting cDNA-AFLP profiles between crown and leaf tissues of cold-acclimated wheat plants indicate differing regulatory circuitries for low temperature tolerance - Seedhabadee Ganeshan; Pallavi Sharma; Lester Young; Ashwani Kumar; D. Brian Fowler; Ravindra N. Chibbar (Plant Molecular Biology, 2011)

Insights into lysosomal cobalamin trafficking: lessons learned from cblF disease - Susann Gailus; Wolfgang Höhne; Bruno Gasnier; Peter Nürnberg; Brian Fowler; Frank Rutsch (Journal of Molecular Medicine, 2010)

The Goals and Research of the BioEnergy Sciences Center (BESC): Developing Cost-effective and Sustainable Means of Producing Biofuels by Overcoming Biomass Recalcitrance - Brian H. Davison; Martin Keller; V. Suzy Fowler (BioEnergy Research, 2009)

Comparative expression of Cbf genes in the Triticeae under different acclimation induction temperatures - Chiara Campoli; Maria A. Matus-Cádiz; Curtis J. Pozniak; Luigi Cattivelli; D. Brian Fowler (Molecular Genetics and Genomics, 2009)

Analysis of severely affected patients with dihydropyrimidine dehydrogenase deficiency reveals large intragenic rearrangements of DPYD and a de novo interstitial deletion del(1)(p13.3p21.3) - André B. P. van Kuilenburg; Judith Meijer; Adri N. P. M. Mul; Raoul C. M. Hennekam; Jan M. N. Hoovers; Christine E. M. de Die-Smulders; Peter Weber; Andrea Capone Mori; Jörgen Bierau; Brian Fowler; Klaus Macke; Jörn Oliver Sass; et al. (Human Genetics, 2009)

Low-temperature acclimation of barley cultivars used as parents in mapping populations: response to photoperiod, vernalization and phenological development - Allen Limin; Ann Corey; Patrick Hayes; D. Brian Fowler (Planta, 2007)

Estimated Sand and Gravel Resources of the South Merrimack, Hillsborough County, New Hampshire, 7.5-Minute Quadrangle - David M. Sutphin; Lawrence J. Drew; Brian K. Fowler (Natural Resources Research, 2007)

Identification of quantitative trait loci and associated candidate genes for low-temperature tolerance in cold-hardy winter wheat - Monica Båga; Sanjay V. Chodaparambil; Allen E. Limin; Marin Pecar; D. Brian Fowler; Ravindra N. Chibbar (Functional & Integrative Genomics, 2006)

Low-temperature tolerance and genetic potential in wheat (Triticum aestivum L.): response to photoperiod, vernalization, and plant development - Allen E. Limin; D. Brian Fowler (Planta, 2006)

In vitro regeneration of cereals based on multiple shoot induction from mature embryos in response to thidiazuron - Seedhabadee Ganeshan; Sanjay V. Chodaparambil; Monica Båga; D. Brian Fowler; Pierre Hucl; Brian G. Rossnagel; Ravindra N. Chibbar* (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

5-Lipoxygenase polymorphism and in-vivo response to leukotriene receptor antagonists - Stephen J. Fowler; Ian P. Hall; Andrew M. Wilson; Amanda P. Wheatley; Brian J. Lipworth (European Journal of Clinical Pharmacology, 2002)

Regulatory role of nitric oxide over hippocampal 5-HT release in vivo - Joanna Segieth; Brian Pearce; Leslie Fowler; Peter S. Whitton (Naunyn-Schmiedeberg's Archives of Pharmacology, 2001)

Phylogeographic differentiation in the mitochondrial control region in the koala, Phascolarctos cinereus (Goldfuss 1817) - Bronwyn A. Houlden; Brian H. Costello; Deirdre Sharkey; Elizabeth V. Fowler; Alistair Melzer; William Ellis; Frank Carrick; Peter R. Baverstock; Martin S. Elphinstone (Molecular Ecology, 1999)
The koala, Phascolarctos cinereus , is a geographically widespread species endemic to Australia, with three currently recognized subspecies: P.c. adustus , P.c. cinereus , and P.c. victor . Intraspecific variation in the mitochondrial DNA (mtDNA) control region was examined in over 200 animals from 16 representative populations throughout the species’ range. Eighteen different haplotypes were defined in the ≈ 860 bp mtDNA control region, as determined by heteroduplex analysis/temperature gradient gel electrophoresis (HDA/TGGE). Any single population typically possessed only one or two haplotypes yielding an average within‐population haplotypic diversity of 0.180 ± 0.003, and nucleotide diversity of 0.16%. Overall, mtDNA control region sequence diversity between populations averaged 0.67%, and ranged from 0% to 1.56%. Nucleotide divergence between populations averaged 0.51%, and ranged from 0% to 1.53%. Neighbour‐joining methods revealed limited phylogenetic distinction between geographically distant populations of koalas, and tentative support for a single evolutionarily significant unit (ESU). This is consistent with previous suggestions that the morphological differences formalized by subspecific taxonomy may be interpreted as clinal variation. Significant differentiation in mtDNA‐haplotype frequencies between localities suggested that little gene flow currently exists among populations. When combined with microsatellite analysis, which has revealed substantial differentiation among koala populations, we conclude that the appropriate short‐term management unit (MU) for koalas is the local population.